2022
DOI: 10.1111/iwj.14046
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in thyroid and parathyroid surgery in Japan: An analysis of the Japan Nosocomial Infections Surveillance database from 2013 to 2020

Abstract: Surgical site infections (SSIs) after thyroid surgery are rare complications, with incidence rates of 0.3%-1.6%. Using a Japanese database, we conducted exploratory analyses on the incidence of SSIs, investigated the incidence of SSIs by the National Nosocomial Infections Surveillance risk index, and identified the causative bacteria of SSIs. SSIs occurred in 50 (0.7%) of 7388 thyroid surgery cases. Risk index-0 patients had the lowest incidence rate of SSIs (0.41%). The incidence of SSIs in risk index-1 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…In this study as well as other studies [42] [45], thyroid surgery performed for malignant neoplastic lesion was found to be is associated with increased risk of postoperative complications. Malignant pathology is associated with increased vascularity, immunosuppression, and poor wound healing predisposing this to increased risk of postoperative complications [45].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this study as well as other studies [42] [45], thyroid surgery performed for malignant neoplastic lesion was found to be is associated with increased risk of postoperative complications. Malignant pathology is associated with increased vascularity, immunosuppression, and poor wound healing predisposing this to increased risk of postoperative complications [45].…”
Section: Discussionsupporting
confidence: 75%
“…Thyroid surgery is considered a clean procedure with a very low incidence of SSIs. The presence of SSIs due to thyroid surgery is a rare complication; however, it is associated with increased morbidity and mortality, increased length of hospital stay, higher readmission rates and increased hospital costs [42]. In this Int.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 An analysis of the Japan Nosocomial Infections Surveillance database from 2013 to 2020 for SSI in thyroid and parathyroid surgery recommend antibiotics for patients with poor general condition and prolonged operative time. 20 In contrary to the recommendations, many centers in Nepal and India, antibiotics are being prescribed for various duration following thyroidectomy. [4][5][6] In an international survey among endocrine surgeons, the patterns of antibiotic use varied widely among European, American and Asian surgeons.…”
Section: Discussionmentioning
confidence: 99%